Value of Open Microcredentials to Earners and Issuers - Danny Young (Athabasca University Press, 2019)
While microcredentials and open digital badges have become increasingly popular in education, more research is needed to better understand their implementation and benefits to both issuers and users. In this paper, we use a case study approach to report and discuss the outcomes from the implementation of an open badges program at National Instruments, highlighting the effects this program has had on both National Instruments and its users. As the program evolves to better meet the needs of its stakeholders, we find that both participants (badge earners) and the issuer (National Instruments) see potential value in the National Instruments Badging Program. The value for both seems to stem from the way in which the program enables the sharing of badges, which helps the earner establish their skills/reputation while also increasing awareness of the program for National Instruments. This study adds to our understanding of why an organization may find value in offering open microcredentials as an alternative to traditional professional development and certificates for their customers and employees.